The Three‐Level Collaboration Exercise – Impact of Learning and Usefulness. (28th January 2015) - Berlin, Johan M.; Carlström, Eric D.
<x xml:space="preserve">Abstract</x> The aim of the study was to examine the emergency personnel's perception of the effects of exercises, with regard to learning and usefulness. The exercises were quasi‐experimental and constructed in such a way that employees from different organizations overlapped each other's tasks. This was accomplished by: having asymmetries included in the scenarios, repeating exercise procedures and testing different strategies, which were discussed at joint seminars. The exercises were compared to a similar study, published in this journal, of nonquasiexperimental but merely traditional exercises. Surveys were distributed and collected from emergency personnel in connection with seven exercises. At the exercises, 94.3% of the personnel thought that the exercises had a focus on collaboration (traditional exercises, 75.6%).